The Relationship Between Macro (Protein, Fat, Carbohydrate) and Micro (Zn) Nutrient Intake With The Incidence Of Stunting Toddlers Aged 24-59 Months In The Working Area Of Tambakrejo Sidoarjo Health Center - Mita Nur Amalina; Luthfi Rusyadi; Taufiqurrahman Taufiqurrahman; Inne Soesanti (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Chronic malnutrition that is still high in Indonesia is stunting. The quality of Human Resources (HR) is affected by the prevalence of stunting in toddlers. One condition is stunting when toddlers experience physical growth delays characterized by a z-score of TB/U is <-2SD. This study determines the relationship between macro (protein, fat, carbohydrate) and micro (Zn) nutrient intake given the prevalence of child stunting in the Tambakrejo Sidoarjo Health Center Work Area. This kind of study employs observational analytical sampling using a sample and the basic random sampling method of 60 toddlers aged 24-59 months. Nutritional intake is obtained by recalling 2x24 hours and stunting incidence data is obtained by measuring height. From stunted toddlers experienced a severe deficit in protein nutrient intake as much as 8 (13.3%). Toddlers with fat intake weight deficit and stunting as many as 16 (16.7%). Toddlers with carbohydrate intake weight deficit and stunting as much as 19 (31.7%), . Toddlers have less zinc intake and stunting by 13 (21.7%). In the working area of the Tambakrejo Sidoarjo Health Center, there is a correlation between the occurrence of stunting toddlers aged 24-59 months and the intake of macronutrients (protein, fat, carbohydrate) and micronutrients (Zn).